2016
DOI: 10.1080/00365521.2016.1256425
|View full text |Cite|
|
Sign up to set email alerts
|

Fatigue in a population-based cohort of patients with inflammatory bowel disease 20 years after diagnosis: The IBSEN study

Abstract: At 20 years after IBD diagnosis, fatigue scores were higher and chronic fatigue was more frequent among IBD patients with active disease than in the reference population and among those with quiescent IBD. Subjectively perceived disease activity, sleep quality, anxiety and depression were associated with fatigue in IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
64
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 50 publications
12
64
1
Order By: Relevance
“…After adjustment for age and sex, fatigue was inversely associated with clinical and endoscopic but not histological remission [7]. In a larger study of the Inflammatory Bowel Disease in South-Eastern Norway (IBSEN) cohort, of the 440 patients with IBD who had disease for at least 20 years and completed the FQ, those with clinically active disease had higher fatigue scores than those with inactive disease (UC 17.1 versus 12.4, p \ 0.001, and CD 17.5 versus 13.3, p \ 0.001) [6]. In a study of patients with IBD in clinical remission, the number of memory T cells and neutrophils was significantly higher (p = 0.005 and 0.033, respectively), while that of monocytes was lower (p = 0.011) in those with fatigue (n = 55) compared with those without fatigue (n = 29), as measured by the CIS-fatigue scale.…”
Section: Pro-inflammatory Statementioning
confidence: 99%
See 2 more Smart Citations
“…After adjustment for age and sex, fatigue was inversely associated with clinical and endoscopic but not histological remission [7]. In a larger study of the Inflammatory Bowel Disease in South-Eastern Norway (IBSEN) cohort, of the 440 patients with IBD who had disease for at least 20 years and completed the FQ, those with clinically active disease had higher fatigue scores than those with inactive disease (UC 17.1 versus 12.4, p \ 0.001, and CD 17.5 versus 13.3, p \ 0.001) [6]. In a study of patients with IBD in clinical remission, the number of memory T cells and neutrophils was significantly higher (p = 0.005 and 0.033, respectively), while that of monocytes was lower (p = 0.011) in those with fatigue (n = 55) compared with those without fatigue (n = 29), as measured by the CIS-fatigue scale.…”
Section: Pro-inflammatory Statementioning
confidence: 99%
“…It occurs in up to 50% of patients with IBD at diagnosis, and is more common in Crohn's disease (CD) (48-62%) than it is in ulcerative colitis (UC) (42-47%) [4]. Multiple studies have shown that fatigue is associated with disease severity [5,6]. One single-center cross-sectional study showed that fatigue has an inverse relationship with clinical and endoscopic remission, and that deep remission has lower rates of fatigue complaints compared to clinical remission only [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaemia is a relatively late stage manifestation of ID; features associated with ID include restless leg syndrome, impaired thermoregulation, impaired immune function, hair loss or glossitis, but importantly fatigue and impaired physical function . Fatigue is a hugely challenging symptom to treat in IBD patients and appears to be associated with additional symptoms including self‐perceived higher disease activity, poor sleep quality, anxiety and depression and increased work impairment . Unsurprisingly, ID has a huge impact on patient‐reported outcomes (PROs) in both IBD and non‐IBD patients, such as quality of life, work capacity, cognitive performances, emotional well‐being and fatigue .…”
Section: Introductionmentioning
confidence: 99%
“…Combining the scores of physical and mental fatigue produces a score for total fatigue, with a maximum score of 33. The questionnaire has been translated into Norwegian and psychometrically tested for validity, reliability, sensitivity, and responsiveness in the Norwegian general population, as well as certain disease cohorts, such as inflammatory bowel disease and non‐Hodgkin lymphoma …”
Section: Methodsmentioning
confidence: 99%